Natural Products Isolation. - Sarker, Satyajit D Latif, Zahid (Humana Press, 2005)
Building on the high reputation of the first edition of Natural Products Isolation, the authors have in this second edition not only significantly updated all the techniques to reflect recent advances in the field, but also added three new chapters on hyphenated techniques, purification by solvent extraction using partition coefficient, and isolation of microbial natural products. These readily reproducible methods make it possible for even the novice to extract, prepare, and isolate natural products from given source materials. The book includes not only powerful cutting-edge techniques, but also simple basic techniques that can save time and effort, as well as achieve results equivalent to using some of the more modern and expensive methodologies. The protocols follow the successful Methods in Biotechnology series format, each offering step-by-step laboratory instructions, an introduction outlining the principles behind the technique, lists of the necessary equipment and reagents, and tips on troubleshooting and avoiding known pitfalls. Up-to-date and highly practical, Natural Products Isolation, Second Edition, offers the aspiring natural products researcher all the information needed to attain mastery of essential methods and the more experienced investigator a useful reference guide to all the available techniques.